Totally laparoscopic total gastrectomy for gastric cancer: Literature review and comparison of the procedure of esophagojejunostomy - Akira Umemura; Keisuke Koeda; Akira Sasaki; Hisataka Fujiwara; Yusuke Kimura; Takeshi Iwaya; Yuji Akiyama; Go Wakabayashi (Asian Journal of Surgery, 2015)
There has been a recent increase in the use of totally laparoscopic total gastrectomy (TLTG) for gastric cancer. However, there is no scientific evidence to determine which esophagojejunostomy (EJS) technique is the best. In addition, both short- and long-term oncological results of TLTG are inconsistent. We reviewed 25 articles about TLTG for gastric cancer in which at least 10 cases were included. We analyzed the short-term results, relationships between EJS techniques and complications, long-term oncological results, and comparative study results of TLTG. TLTG was performed in a total of 1170 patients. The mortality rate was 0.7%, and the short-term results were satisfactory. Regarding EJS techniques and complications, circular staplers (CSs) methods were significantly associated with leakage (4.7% vs. 1.1%, p < 0.001) and stenosis (8.3% vs. 1.8%, p < 0.001) of the EJS as compared with the linear stapler method. The long-term oncological prognosis was acceptable in patients with early gastric cancers and without metastases to lymph nodes. Although TLTG tended to increase surgical time compared with open total gastrectomy and laparoscopy-assisted total gastrectomy, it reduced intraoperative blood loss and was expected to shorten postoperative hospital stay. TLTG is found to be safer and more feasible than open total gastrectomy and laparoscopy-assisted total gastrectomy. At present, there is no evidence to encourage performing TLTG for patients with advanced gastric cancer from the viewpoint of long-term oncological prognosis. Although the current major EJS techniques are CS and linear stapler methods, in this review, CS methods are significantly associated with leakage and stenosis of the EJS.